1991
DOI: 10.1103/physrevlett.67.664
|View full text |Cite
|
Sign up to set email alerts
|

Semiclassical dynamics of chaotic motion: Unexpected long-time accuracy

Abstract: Chaos introduces essential complications into semiclassical mechanics and the conventional wisdom maintains that the semiclassical time-dependent Green's function fails to describe the quantum dynamics once the underlying chaos has had time to develop much finer structure than a quantum cell ih). We develop a method to evaluate the semiclassical approximation and test it for the first time under these circumstances. The comparison of the quantum and semiclassical dynamics of the stadium billiard shows remarkab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
184
0
1

Year Published

1994
1994
2018
2018

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 225 publications
(189 citation statements)
references
References 6 publications
4
184
0
1
Order By: Relevance
“…Hence, the VVG propagator, which puts zero amplitude in the classically forbidden region, becomes inadequate to describe the dynamics of the wave packet after the exit event. We point out that this failure of the VVG propagator is not necessarily inconsistent with the long-time accuracy achieved by Heller and Tomsovic [11] in the case of the stadium billiard. Since the amplitude in the forbidden regions is evidently negligible in that problem [4], it follows that the stretching of the exponential tail and associated phenomena that we observe must not be significant there.…”
Section: Introductionsupporting
confidence: 55%
“…Hence, the VVG propagator, which puts zero amplitude in the classically forbidden region, becomes inadequate to describe the dynamics of the wave packet after the exit event. We point out that this failure of the VVG propagator is not necessarily inconsistent with the long-time accuracy achieved by Heller and Tomsovic [11] in the case of the stadium billiard. Since the amplitude in the forbidden regions is evidently negligible in that problem [4], it follows that the stretching of the exponential tail and associated phenomena that we observe must not be significant there.…”
Section: Introductionsupporting
confidence: 55%
“…Some time later, Tomsovic and Heller [5] showed that even for those long times, for which classical fine structure had developed on a scale much smaller thanh, the semiclassical propagation of the packet can be carried out with good precission, by computing the corresponding correlation function, C scl (t), as a sum of contributions of the homoclinic excursions of the PO. This procedure has nevertheless some drawbacks, since for example the number of orbits that is necessary to include in the calculation to obtain converged results grows dramatically with time.…”
Section: Introductionmentioning
confidence: 99%
“…They give rise to different homoclinic orbits in Eq. (27) since 0γ0 = 0100010 0γ 0 = 0110 (29) which do lead to differing quality of approximation. The 10001 orbit, starts from point (3.18110104534044, 3.18110104534044) and maps back into itself to 12 decimal places in a double precision calculation after 5 iterations.…”
Section: Optimal Representation and Numerical Verificationmentioning
confidence: 99%
“…In the semiclassical regime, properties of such classical orbits are also extremely important. A few cases are given by periodic [23][24][25] and closed orbit sum rules [26][27][28] that determine quantal spectral properties, and homoclinic (heteroclinic) orbit summations [29,30] generating wave packet propagation approximations. The interferences in such semiclassical sum rules are almost exclusively governed by the orbits' classical action functions and Maslov indices [31][32][33], and thus this information takes on greater importance in the context of the asymptotic properties of quantum mechanics.…”
Section: Introductionmentioning
confidence: 99%